Perceptions of Indonesian multilingual scholars about preparing and publishing research manuscripts in international journals - Zifirdaus Adnan; Safnil Arsyad; Bambang Kaswanti Purwo; Katharina Endriati Sukamto (Studies in English Language and Education, 2021)
There has been a great deal of interest in issues multilingual scholars (henceforth: MLS) have in trying to gain publication in international main-stream English language journals (IEJs). However, little research has been published on the experience of MLS using their perspective, particularly how they perceive their competence (knowledge and skills) to publish their research internationally. The purpose of this study was to fill this gap by investigating what they perceived as the factors that inhibited them from publishing in IEJs. This study mainly used a quantitative method, but the results were supplemented with interviews and focus group discussion with some of the participants in the survey. Principal Component Analysis (PCA) tool of the SPSS statistical programme was used to conduct two levels of analysis: the PCA and Confirmation Factorial Analysis (CFA). The key finding was that the most critical factor for the participants was not a lack of funds as widely reported in many previous studies, but lack of competence to face the challenges of preparing and publishing research article (RA) in IEJs, which had dampened self-confidence. The low self-confidence and two solutions, suggested by the participants, implicitly confirmed the key finding. The participants were aware of the various benefits of research article publication in IEJs, but they were not strong enough to overcome the critical factor. The implication is that policymakers should consider providing regular training for staff with adequate practice and feedback and introducing the subject to undergraduate or, at least, MA students before they embark on starting their research projects.